3D Printing Hierarchical Silver Nanowire Aerogel with Highly Compressive Resilience and Tensile Elongation through Tunable Poisson's Ratio. Issue 38 (18th August 2017) - Yan, Pengli; Brown, Emery; Su, Qing; Li, Jun; Wang, Jian; Xu, Changxue; Zhou, Chi; Lin, Dong
Abstract : Metallic aerogels have attracted intense attention due to their superior properties, such as high electrical conductivity, ultralow densities, and large specific surface area. The preparation of metal aerogels with high efficiency and controllability remains challenge. A 3D freeze assembling printing technique integrated with drop‐on‐demand inkjet printing and freeze casting are proposed for metallic aerogels preparation. This technique enables tailoring both the macrostructure and microstructure of silver nanowire aerogels (SNWAs) by integrating programmable 3D printing and freeze casting, respectively. The density of the printed SNWAs is controllable, which can be down to 1.3 mg cm −3 . The ultralight SNWAs reach high electrical conductivity of 1.3 S cm −1 and exhibit excellent compressive resilience under 50% compressive strain. Remarkably, the printing methodology also enables tuning aerogel architectures with designed Poisson's ratio (from negative to positive). Moreover, these aerogel architechtures with tunable Poisson's ratio present highly electromechanical stability under high compressive and tensile strain (both strain up to 20% with fully recovery). Abstract : Silver nanowire aerogels printed by a newly developed 3D freeze assembling printing technique (with controllable density down to 1.3 mg cm −3 ) reach high electrical conductivity of 1.3 S cm −1 and exhibit excellent compressive resilience under 50% compressive strain. Remarkably, the tensile strain is greatly improved by tuning with Poisson's ratio of the aerogel from negative to positive.